1997
DOI: 10.1073/pnas.94.2.575
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the chicken β-globin insulator

Abstract: Insulators, first identified in Drosophila, are DNA sequence elements that shield a promoter from nearby regulatory elements. We have previously reported that a DNA sequence at the 5 end of the chicken ␤-globin locus can function as an insulator. It is capable of shielding a reporter gene from the activating effects of a nearby mouse ␤-globin locus control region element in the human erythroleukemic cell line K562. In this report, we show that most of the insulating activity lies in a 250-bp CpG island (core e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
359
3
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 365 publications
(371 citation statements)
references
References 25 publications
7
359
3
2
Order By: Relevance
“…Prior studies on cHS4 insulators showed that deletion of the CTCF binding sites was associated with loss of enhancer-blocking activity, but did not alter the barrier function of the element. 22,46 However, earlier work on the natural cHS4 locus could not readily assess a potential silencing effect of CTCF in addition to its enhancer-blocking activity. 27 Analysis of CTCF in several genomic contexts brought forward its key function in the organization of the chromatin architecture.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies on cHS4 insulators showed that deletion of the CTCF binding sites was associated with loss of enhancer-blocking activity, but did not alter the barrier function of the element. 22,46 However, earlier work on the natural cHS4 locus could not readily assess a potential silencing effect of CTCF in addition to its enhancer-blocking activity. 27 Analysis of CTCF in several genomic contexts brought forward its key function in the organization of the chromatin architecture.…”
Section: Discussionmentioning
confidence: 99%
“…2,10,[15][16][17][18][19] Previous reports have shown that HS4 insulator protects transgenes from position effect variegation when introduced into MoMLV-based retroviral vectors. 20,21 Since the HS4 fragment is active in restricted cell types, 21 a quest for alternative insulators is necessary to propagate the use of the insulator in various cell types and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…15 The chicken bglobin HS4 insulator elements functionally block enhancer elements when positioned between the promoter and enhancer and have been shown to protect tissue-specific or -inducible promoters in adenovirus backbones. 13,15,[29][30][31] Therefore, we wanted to determine if inclusion of the chicken b-globin HS4 insulator element with our promoter construct could eliminate any potential interference encountered by the adenoviral vector. Extreme efforts were made to incorporate a 1.2 kbp HS4 element both upstream and downstream of the INSM1 promoter-luciferase 2 constructs.…”
Section: Resultsmentioning
confidence: 99%